Autogenous Dentin Block of a Non‐Restorable Wisdom Tooth for Localized Horizontal Ridge Augmentation: Radiographic and Histological Analysis – A Preliminary Case Report. Issue 2 (5th November 2020) - Elraee, Leila; Moussa, Mahmoud; Adel‐Khattab, Doaa
Abstract : Introduction: Tooth roots proved in different studies clinically and radiographically to be an alternative to autogenous bone. However, the histological evaluation of the tooth block following ridge augmentation is still missing. The aim of this case report was to evaluate histologically and radiographically the effect of autogenous dentin block (DB) to restore a horizontal ridge deficiency at a single tooth gap. Case Presentation: A healthy 36‐year‐old female patient presented with a missing lower first molar (30), after clinical and radiographic examination, the site showed a class III defect horizontal atrophy. The procedure performed was the surgical removal of the wisdom tooth (32), shaping and fixation of a separated DB at the defect site using an osteosynthesis screw. A cone beam computed tomography was performed immediately and 6 month following the surgery. During implant placement, a core biopsy specimen was retrieved, stored and prepared for histological evaluation. The radiographic analysis showed a horizontal width gain of about 4 mm. The histologic assessment revealed cortical bone formation at the buccal and lingual aspects between the tooth and the bone. During implant placement, the core biopsy exhibited a slight separation upon removal from the grafted side, at 6 month following implant placement, the implant was successfully osteointegrated. Conclusion: DB was successfully used for horizontal alveolar ridge augmentation, thus allowing a prosthetically driven implant placement. More cases assessing implant survival and success are needed to confirm the results of this case report.